Respuesta :

Wolfyy

Hey!

-------------------------------------------------

I'm going to assume that the value of t is x.

-------------------------------------------------

Steps To Solve:

3(x - 2) = 6

~Distributive Property

→ 3x - 6 = 6

~Simplify

→ 3x + (-6) = 6

~Add 6 to both sides

→ 3x + (-6) + 6 = 6 + 6

~Simplify

→ 3x = 12

~Divide 3 to both sides

→ 3x/3 = 12/3

~Simplify

→ x = 4

-------------------------------------------------

Hence, x equals 4!

-------------------------------------------------

Hope This Helped! Good Luck!

ACCESS MORE